Raising public awareness to break the chain of the spread of COVID-19 in Cibungur Village, Parungponteng District - Fahmi Sidiq (International Journal of Research in Community Services, 2022)
Corona virus or covid-19 is a viral infection that was discovered at the end of 2019 in the city of wuhan, China. The massive spread has made more than 900,000 Indonesians infected with COVID-19. Nevertheless, there are several ways that can be done to reduce the risk and prevent transmission, one of which is the implementation of Clean and Healthy Lifestyle (PHBS), the use of hand sanitizers and masks. Community service is carried out in Cibungur Village, Parungponteng District. Cibungur village is one of the vulnerable places in the transmission of COVID-19. This is because there are so many people from villages who work in urban areas, so the risk of spreading it is very vulnerable. Therefore, the University Pharmacy Study Program took the initiative to provide community service by providing hand sanitizers and masks as an effort to implement clean and healthy living behaviors, as well as efforts to break the COVID-19 chain.